Exceptionally high foraminiferal dissolution in the western Bay of Bengal. (December 2022) - Bhadra, Sudhira R.; Saraswat, Rajeev
Abstract: The planktic foraminifera are an important component of the global carbon cycle, as they sequester the carbon, thus burying it in the sediments for ages. The burial of planktic foraminiferal shells, however, depends on the carbonate chemistry of the deep ocean. A significant fraction of foraminiferal shells dissolves well above the carbonate compensation depth. The foraminiferal lysocline is defined to delineate such zones of planktic foraminiferal dissolution well above the carbonate compensation depth. The dissolution of carbonate above the lysocline, termed supralysoclinal dissolution, has also been reported from highly productive basins. This study demarcates the extent of foraminiferal dissolution in the western Bay of Bengal. We document the distribution of planktic foraminifera and shell fragments in 100 core top samples collected from the coast perpendicular transects at depths ranging from 27 m to 2760 m. We examine the possible reasons for the foraminiferal dissolution by comparing the foraminiferal indices with the ambient bottom water parameters. The absolute abundance of planktic foraminifera is significantly low, both on the continental shelf and below ∼1000 m. The low abundance on the shelf is due to the terrigenous dilution. The fragmentation indices and the ratio between dissolution resistant and dissolution susceptible assemblage, however, confirm a significant increase in the dissolution at depths deeper than 1000 m. The foraminiferal shell dissolution at deeper depths is due to the high pressure, whereas the biogenic respiration-induced calcite under-saturation is responsible for the significant dissolution at a very shallow depth in the western Bay of Bengal, as compared to other parts of the world ocean. Graphical Abstract: ga1 Highlights: Increased foraminiferal dissolution below 1000 m water depth in the western Bay of Bengal. Dissolution is attributed to a combined effect of shallow lysocline and supralysoclinal dissolution. Anthropogenic CO2 sink and methane seepage also contribute to the foraminiferal dissolution.